Characterizing Undernourished Children Under-Five Years Old with Diarrhoea in Mozambique - Sambo, Júlia (2022)
792. The Global Alliance for Vaccine and Immunization through the Health System Strengthening (HSS) project. The Flandres Government, BICMINS project. The Calouste Gulbenkian Foundation from where J?lia Sambo, Marta Cassocera and Assuc?nio Chissaque have a PhD fellowship. Acknowledgments: We would like to thank the parents or guardians who consented for their children to be enrolled in the surveillance and all ViNaDia team for their dedication and effort with recruitment, data collection and shipment of specimens to the central laboratory in Maputo: Miguel Bambo, Carlos Guilamba, Celina Nhamuave, M?rcia Nhaca, Judite Sal?ncia, Herm?nio Cossa, F?lix Gundane, Aun?sia Marurele, Angelina Pereira, Mulaja Kabeya ?tienne, Celso Gabriel, Titos Maulate, Julieta Ernesto, Siasa Mendes, H?rcio Simbine, Susete de Carvalho, Marcos Joaquim, Elvira Sarguene, Fernando Vilanculos, Felicidade Martins, Dulce Gra?a, Edma Samuel, Vivaldo Pedro, L?cia Matabel, Aida Junta, Gilda Maria Safrina, Nat?rcia Abreu, Vanessa da Silva, Nazareth Mabutana, Delcio Muteto, Benilde Munlela and Carolina Conjo. A special thank you also to Timothy Kellogg for all the guidance during the initial data analysis process. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.